Is genital tract infection related to tubal diseases in infertile Vietnamese women? - Minh Tam Le; Thi Le Na Nguyen; Duong Dinh Le; Tram Viet Quynh Ngo; Anh Thi Chau Nguyen; Bach Hoang Nguyen; Huy Vu Quoc Nguyen; Thanh Ngoc Cao; Andres Salumets; Reet Mändar (Journal of Infection in Developing Countries)
Introduction: The goal of this study was to identify the profile of genital tract infections and their relationship with clinical and demographic parameters as well as tubal diseases among infertile women in Vietnam.